Functional availability analysis of discrete transport system simulated by SSF tool. (22nd February 2010) - Walkowiak, Tomasz; Mazurkiewicz, Jacek
The paper presents an approach to availability calculation of discrete transport system (DTS). The system is described by the formal model, which includes reliability and functional parameters of DTS. The availability and average availability of the system – defined in a functional way – is discussed as a function of different essential parameters when the DTS is organised. The proposed analysis is based on the modelling and simulating of the system behaviour. Monte Carlo simulation is used to encourage reliability and stochastic functional parameters. The simulator is built using scalable simulation framework (SSF). No restriction on the system structure and on a kind of distribution is the main advantage of the method. The paper presents some exemplar system modelling and results.